LEGAL REGULATION OF RELATIONS DURING THE RECOVERY OF COMPENSATION FOR A FLIGHT DELAY - Хом’яченко, Світлана Іванівна; Хоцяновська, Наталія Францівна; Часова, Тетяна Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the study attempts to determine the scope of legal regulation of relations in the recovery of compensation for the delay of the flight, as well as the complications and problems associated with the lack of appropriate legal regulation faced by passengers in the event of recovery of such compensation, and possible ways of eliminating the relevant obstacles in realization by passengers of this right. Methods of research: in the work the dialectical method of cognition, general scientific and special methods were used. Results: the reasons for the need to form a centralized mechanism for realizing the passenger right to compensation in connection with flight delay are given. Discussion: search for ways to improve the legal mechanism for implementing passenger rights to compensation in connection with flight delays. Summing up these considerations, it can be stated that despite the certain level of legal regulation of national and legislative norms during the realization of passengers’ right to compensation in connection with the delay of the flight, such complications as: uncertainty of the form and content of the documents, which is the basis for Compensation; refusal of the employees of the air carrier or the airport to certify the fact of the timely appearance of passengers for registration and the fact of the flight delay; their failure to fulfill their duties to inform passengers about flight delays, failure to report the reasons and possibilities for the effective realization of the right to such compensation; abstract determination of time delay countdown and others. Elimination of these complications is possible through the formation and legislative consolidation of a unified centralized mechanism for the implementation of the relevant provisions of legislative acts on the right of passengers for reimbursement in connection with flight delays, which will also contribute to the modernization of the transport system of Ukraine.